Errors of interpretation and modeling: A reply to Grinband et al. - Yeung, Nick (2011)
Grinband et al., 2011 compare evidence that they have collected from a neuroimaging study of the Stroop task with a simulation model of performance and conflict in that task, and interpret the results as providing evidence against the theory that activity in dorsal medial frontal cortex (dMFC) reflects monitoring for conflict. Here, we discuss several errors in their methods and conclusions and show, contrary to their claims, that their findings are entirely consistent with previously published predictions of the conflict monitoring theory. Specifically, we point out that their argument rests on the assumption that conflict must be greater on all incongruent trials than on all congruent trials—an assumption that is theoretically and demonstrably incorrect. We also point out that their simulations are flawed and diverge substantially from previously published implementations of the conflict monitoring theory. When simulated appropriately, the conflict monitoring theory predicts precisely the patterns of results that Grinband et al. take to present serious challenges to the theory. Finally, we note that their proposal that dMFC activity reflects time on task is theoretically weak, pointing to a direct relationship between behavior (RT) and neural activity but failing to identify any intervening psychological construct to relate the two. The conflict monitoring theory provides such a construct, and a mechanistic implementation that continues to receive strong support from the neuroimaging literature, including the results reported by Grinband et al.